Candy slain murder ebook A jolly & delightful cozy mystery. - Day, Maddie (Country Store Mystery, 2020)
An entertaining series perfect for fans for Joanne Fluke that highlights delicious new recipes for you to try this holiday season! A merry Christmas mystery is the festive read you need this time of year... "The lavish food descriptions and appended recipes are the best parts." — Kirkus Reviews Christmas cheer has sent the griddle into overdrive at Robbie Jordan's popular country store and café . And this year, there's a new seasonal special to feast on: murder... As December sweeps through South Lick, Indiana, Robbie's life seems merry and bright like the string lights glistening around town. But strange happenings signal a bumpy ride into the holidays. First a man raises eyebrows at Pans 'N Pancakes when he claiming to be the long-lost half-brother of Robbie's assistant. Then a fire destroys the home of a controversial anesthesiologist, exposing skeletal remains in his attic. Helplessly intrigued, all Robbie wants for Christmas is to stop her winter wonderland from becoming a real nightmare. With a decades-old mystery taking shape, can she run as fast as she can in pursuit of a killer who's harder to crack than a stale gingerbread man?